Phytochemical characterisation for industrial use of pomegranate (Punica granatum L.) cultivars grown in Spain - Mena, Pedro; Garcia-Viguera, Cristina; Navarro-Rico, Javier; Moreno, Diego A.; Bartual, Julián; Saura, Domingo; Marti, Nuria (2017)
BACKGROUND: The study of 15 pomegranate cultivars was carried out in order to demonstrate the wide diversity among the quality of Spanish pomegranates, and compared to 'Wonderful' cultivars, which are used worldwide for industrial purposes. Juice yield, quality parameters, organic acids and sugars, colour, vitamin C, ellagic acid, punicalagins, anthocyanins, total phenolic content, antioxidant capacity, and sensory properties were measured. RESULTS: A considerable variation was found between 'Wonderful' and pomegranates of Spanish origin, according to both cluster analysis and principal component analysis. 'Wonderful' juices displayed large antioxidant activity and a polyphenol content with very high acidity. In contrast, 'Mollar de Elche' showed fewer anthocyanins although it had very superior organoleptical properties. In addition to a high content in ellagitannins, 'Valenciana' juices had exclusive colour parameters. CONCLUSION: These useful results can be employed by the juice processing industry to select those properties more interesting for the development of pomegranate juices that are organoleptically attractive and rich in bioactive compounds. (C) 2011 Society of Chemical Industry